The effect of incorporation Nano Cinnamon powder on the shear bond of the orthodontic composite (an in vitro study) - Saba N. Yaseen; Amer A. Taqa; Ali R. Al-Khatib (Journal of Oral Biology and Craniofacial Research)
Objectives: One of the causes of dental caries that occurs due to orthodontic treatment is the lack of antibacterial properties in orthodontic adhesive. This study was designated to investigate the effect of orthodontic resin modified by incorporating Nano Cinnamon powder on the shear bond strength of orthodontic brackets. Materials and methods: Heliosit Orthodontic Resin, a photo-activated light cure resin was modified by the addition of Cinnamon in the form of Nano particle powder. Twenty uniform disks were made, 5 as a control and 5 for each concentration of the 1%, 3% and 5% wt/wt Cinnamon modified resin. Their antimicrobial activity against Streptococcus Mutans was tested using the disk diffusion method. Then, the most effective concentration of the modified resin was used to bond metal orthodontic brackets to human extracted premolars. The universal testing machine was used to record the shear bond strength of the control and the modified resin. Also, the adhesive remnant index was measured. Results: Disc diffusion method showed that the 3% wt/wt Cinnamon powder modified resin was more effective than 1% with a larger bacterial inhibition zone. Shear bond strengths of the control were 8.50 MPa and 7.20 MPa for the 3% Cinnamon modified resin with no significant difference between them. Also, no significant difference was recorded in the adhesive remnant index scores between the control and the modified resin groups. Conclusion: Findings of this study revealed that the incorporation of 3% Cinnamon Nano particles in orthodontic resin produced an antibacterial effect against Streptococcus mutans without compromising the shear bond strength. Clinical relevance: Incorporation of Cinnamon Nano particles in orthodontic resin may reduce caries formation around brackets during treatment course.